2019
DOI: 10.1177/0886260519888525
|View full text |Cite
|
Sign up to set email alerts
|

What is Violence? The Role of Sexism and Social Dominance Orientation in Recognizing Violence Against Women

Abstract: Violence against women represents a global public health issue of epidemic proportions, as well as a gross violation of women’s human rights. It can take many forms, such as physical aggression, sexual coercion, psychological abuse, and controlling behaviors. The purpose of the study was to extend past research on recognition of violence against women within the framework of the ambivalent sexism theory and the social dominance orientation (SDO) theory. Specifically, we investigated the following: (a) to what … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
1
15

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 35 publications
4
28
1
15
Order By: Relevance
“…As seen from the results of descriptive statistics, men were more hostile and benevolent toward women, as well as more benevolent toward men when compared with women. These findings are consistent with previous research [59,66,67] and suggest that the endorsement of sexist attitudes differs according to gender. As sexism relegates women to hierarchically lower positions than those of men, it seems reasonable than men are more prone to sexist attitudes toward women.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…As seen from the results of descriptive statistics, men were more hostile and benevolent toward women, as well as more benevolent toward men when compared with women. These findings are consistent with previous research [59,66,67] and suggest that the endorsement of sexist attitudes differs according to gender. As sexism relegates women to hierarchically lower positions than those of men, it seems reasonable than men are more prone to sexist attitudes toward women.…”
Section: Discussionsupporting
confidence: 93%
“…[58] concluded that people who scored higher in benevolent sexism tended to excuse the rapist more often than those who scored lower in benevolent sexism. Along similar lines, since ambivalence toward men reinforces gender hierarchy by characterizing men as inherently powerful and aggressive while admiring their traditional roles [59], it is expected that these beliefs also influence perceptions about sex offenders. To our knowledge, no studies have examined the impact of ambivalent sexism as a moderator of the perceptions toward sex offenders.…”
Section: Other Attitudinal and Personal Factors Influencing Public Attitudes And Perceptions About Sex Offendersmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, they may even be present, albeit indirectly, in the health education received [ 20 ]. The assimilation of such ideas is the perfect breeding ground for the development of tolerance towards abuse, thus ensuring that historical levels of gender violence continue to be breached year after year [ 15 , 21 ] and blurring the lines between what adolescents consider to be abuse and that normal behavior [ 22 ].…”
Section: Introductionmentioning
confidence: 99%